Trends in Learning Environment Research for Contemporary Educational Needs in Elementary and Secondary Education - EGI, Hironori; SETOZAKI, Norio; NEMOTO, Junko; INAGAKI, Tadashi; MITSUI, Kazuki; NAKAYA, Kae; IKEJIRI, Ryohei (Japan Journal of Educational Technology, 2024)
In contemporary primary and secondary education, social needs and technological environments for learning environments are changing. We reviewed research trends on learning environments in Japan, taking as our guide the four aspects of “space”, “artifact”, “activity”, and “community” as described by Yamauchi (2020). First, we surveyed which academic fields of learning environments were the subject of research, and found that the largest number of papers were from the Japan Society for Educational Technology, focusing on “artifacts” and “activities”. Second, a review of only papers from the Japan Society for Educational Technology (JSET) verified that there was a situation where research on “community” and “space” was scarce, along with the typical combination of the four aspects. Based on these results, we recommended (1) an approach to areas where knowledge is lacking and (2) the importance of constructing a framework to systematically capture the accumulated knowledge.